Evaluation of the Effectiveness of Treatment of Patients with Acute Sensorineural Hearing Loss - Takhsinovna, Nasretdinova Makhzuna; Alisherovich, Normuradov Nodirjon; Nazarovna, Normirova Nargiza (American Journal of Bioscience and Clinical Integrity, 2025)
The article describes the results of treatment of patients with acute sensorineural hearing loss of different age groups. The results of hearing restoration depending on the cause of neurosensory disturbance, the timing of treatment and the ways of introducing glucocorticosteroids were analyzed.